Polymorphisms in Dopaminergic Genes in Schizophrenia and Their Implications in Motor Deficits and Antipsychotic Treatment - Ye, Jiaen; Ji, Feng; Jiang, Deguo; Lin, Xiaodong; Chen, Guangdong; Zhang, Wei; Shan, Peiwei; Zhang, Li; Zhuo, Chuanjun (Frontiers in Neuroscience, 2019)
Dopaminergic system dysfunction is involved in the pathogenesis of schizophrenia (SCZ) and can mediate SCZ-related motor disorders. Recent studies have gradually revealed that SCZ susceptibility and associated motor symptoms can be mediated by genetic factors, including dopaminergic genes. More importantly, polymorphism of those genes seems to be associated with both sensitivity to and the adverse effects of antipsychotic drugs. The study of genetic polymorphisms in the dopaminergic system may help to optimize individualized drug strategies across SCZ patients.This review summarizes current progress in the involvement of the dopamine system in motor disorders associated with SCZ and the motor-related adverse effects after antipsychotic treatment, with a special focus on the genetic polymorphism of dopaminergic genes. We hypothesize that the genetic profile of the dopaminergic system mediates both the motor deficits associated with SCZ and the adverse effects of antipsychotics. The study of dopaminergic gene polymorphisms may help to predict drug efficacy and to decrease adverse effects, thus optimizing treatment strategies.